The Failure of the Washington Consensus, the Need for a New Reform and the Rise of the Beijing Consensus - Arifin, Bustanul (AEGIS : Journal of International Relations, 2017)
Global economic policy dominated by the influence of the Washington Consensus during the past few decades has led to many upheavals in the global economic order. The term Washington Consensus is associated with three major institutions located in Washington, the World Bank, the International Monetary Fund (IMF), and the US Treasury Department, and it has become a neoliberal economic agenda also called as the western economic agenda. The debates are increasing significantly regarding the effectiveness of policies that are sourced from the World Bank, IMF and the US Treasury Department in encouraging development. Where in reality, those countries that adopt the recommendations derived from the Washington Consensus, mostly bring them to experience economic problems. The last example is believed to be the 2008 global financial crisis.In this journal, the author will explain and analyse the definition and the recommendations offered by the Washington Consensus in order to promote global development. It will also present various criticisms that have emerged from the various parties to the Washington Consensus. Various analysis will also be given to understand that the Washington Consensus is already less suitable and appropriate for use to encourage the global development today. Then this journal confirms the need for a new reform of the global economic order, namely with the policy recommendations for the new global economy through a new consensus. The rapid development of globalization has changed characteristic of many countries, especially developing countries, so that many developing countries begin to look for new formulas to boost their economies. Because the Washington Consensus is seen only benefit developed countries, while developing countries and least developed countries are experiencing a lot of problems of development. Thus, due to the demand and push for a reformation of the global economic order, China and the countries of the region have established the Asian Infrastructure Investment Bank (AIIB), based in Beijing, and it is now often called as the Beijing Consensus. Then, it now becomes a real sign of resistance to the Washington Consensus.